Prácticas, saberes y sensibilidades de la pesca artesanal en Nuquí: una alternativa al desarrollo (2021)
Historically the Colombian North Pacific, due to its immense cultural and biological diversity, has been the focus of development discourses that, focused on a capitalist logic of appropriation and exploitation of natural resources, ignores the ways of living, being and understanding the world of Afro-descendant communities. Around artisanal fishing other forms of social, economic and political organization are consolidated. This research sought to understand artisanal fishing in Nuquí, Chocó, as an alternative to development, for which it was based on a qualitative methodology of case study between 2018 and 2019. The emphasis is placed on artisanal fishing in Nuquí as an alternative to development that incorporates their own visions of well-being based on respect for the territory, materializes processes of marine-coastal governance in socially, culturally and environmentally situated contexts, and recognizes a local economy based on their own production processes that strengthen their food sovereignty.